Risk factors for respiratory morbidity in infancy after very premature birth. Issue 4 (5th May 2005) - Greenough, A; Limb, E; Marston, L; Marlow, N; Calvert, S; Peacock, J
Abstract : Objectives: To determine the occurrence of respiratory morbidity during infancy after very premature birth and to identify risk factors. Design: Prospective follow up study. Setting: The United Kingdom oscillation study. Patients: 492 infants, all born before 29 weeks gestation. Interventions: Structured questionnaires were completed by local paediatricians when the infants were seen in outpatients at 6 and 12 months of age corrected for prematurity. Main outcome measures: Cough, wheeze, and treatment requirements and the composite measure of respiratory morbidity (cough, frequent cough, cough without infection, wheeze, frequent wheeze, wheeze without infection, and use of chest medicine) and their relation to 13 possible explanatory variables. Results: At 6 and 12 months of corrected age, 27% of the infants coughed and 6% had frequent (more than once a week) cough, and 20% and 3% respectively had wheeze or frequent wheeze. At 6 and 12 months, 14% of infants had taken bronchodilators and 8% inhaled steroids. After adjustment for multiple outcome testing, four factors were associated with increased respiratory morbidity: male sex, oxygen dependency at 36 weeks postmenstrual age, having older siblings aged less than 5 years, and living in rented accommodation. Conclusions: Male infants are particularly vulnerable to respiratory morbidity in infancy after very premature birth. It is important to identify a safe and effective strategy to prevent chronic oxygen dependency.